A study of risk management in it system towards a better performance in organization - Su, Hui Min (2015)
The risk in IT system may influence the performance of the organization. In this study, it discusses about the type of risks in IT system and the impact of risk management in IT system towards organization. The scope of this study is focusing on a manufacturing company which using IT system for their daily tasks in order to examine the type of risks in IT system and the impact of the risk management in IT system. A questionnaire has been sent to the respondents and interview was conducted to find out the type of risks and impact of risk management in IT system. There was 20 respondents had participant in this research.